Procedures preparatory to setting up a luminescence pulsing system - Chithambo, M. L. (Ancient TL, 2005)
Some key tests necessary in the setting up of a luminescence pulsing system are presented. The procedures discussed are concerned with measurement of reliable luminescence-photon counting rates whose analyses provide information about lifetimes and intensity of luminescence measured using pulsed optical stimulation. The paper presents data from a measurement system which used a time-to-amplitude converter for timing.